Selected innovation strategies of the transport and hotel industries as a response to the rise of disruptive technologies uber and airbnb through environmental scanning and comparative analysis implications for the Philippines' strategy - Mahusay, Ezra Mae; Imbang, Glen (Quezon City University of the Philippines Diliman, 2016)
Sharing economy is defined as an economic model in which individuals are able to borrow or rent assets owned by someone else for a fee. The rise of smartphones gave birth to two digital sharing economy platforms-Uber and Airbnb.

Uber is a ride-hailing application that allows riders to book a ride thru the application. Additionally, it allows drivers with professional licenses to be a part time driver/operator. Airbnb is an application that allows owners to list and rent out their homes or rooms. Both applications have caused controversies from their traditional counterparts- the transport and hotel industry.

This research paper intends to understand how disruptive technologies can impact the market and how different countries respond to them. The result will be used to come up with an analysis and comparison of the different responses as an innovation strategy.

The paper uses tools like survey, research and environmental scanning to gather all information required for the study. The results and analyses of the research paper will help assess the current innovation strategy used by the country to respond to these technologies and come up with recommendations on how to improve or revise them.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Technological innovations; Disruptive technologies; Environmental scanning; Uber; Airbnb